2020
DOI: 10.1186/s12862-020-1582-1
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Taxus cuspidata (Taxaceae): eight protein-coding genes have transferred to the nuclear genome

Abstract: Background: Gymnosperms represent five of the six lineages of seed plants. However, most sequenced plant mitochondrial genomes (mitogenomes) have been generated for angiosperms, whereas mitogenomic sequences have been generated for only six gymnosperms. In particular, complete mitogenomes are available for all major seed plant lineages except Conifer II (non-Pinaceae conifers or Cupressophyta), an important lineage including six families, which impedes a comprehensive understanding of the mitogenomic diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 94 publications
6
75
0
Order By: Relevance
“…As part of the genome annotation process, we inferred RNA editing sites for protein-coding genes. The number of RNA editing sites predicted by PREP-Mt for the protein-coding genes of the Siberian larch mitogenome was within the range predicted with the same cut-off 0.2 in other gymnosperms, but varied greatly between different species from 225 in Welwitschia to 1102 in Taxus, 1179 in Pinus, 1206 in Cycas, and 1306 in Ginkgo (see Table 1 in [34]. The number of RNA editing sites correlated neither with mitogenome size nor with GC content, but more data are needed to make stronger conclusions.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…As part of the genome annotation process, we inferred RNA editing sites for protein-coding genes. The number of RNA editing sites predicted by PREP-Mt for the protein-coding genes of the Siberian larch mitogenome was within the range predicted with the same cut-off 0.2 in other gymnosperms, but varied greatly between different species from 225 in Welwitschia to 1102 in Taxus, 1179 in Pinus, 1206 in Cycas, and 1306 in Ginkgo (see Table 1 in [34]. The number of RNA editing sites correlated neither with mitogenome size nor with GC content, but more data are needed to make stronger conclusions.…”
Section: Discussionmentioning
confidence: 52%
“…The reasons for extremely large size of mitogenomes in plants are still not fully understood, but at least can be partly explained by a variable number of mobile genetic elements, introns and plasmid-related sequences [51] and could be affected by different factors, such as proliferation of retrotransposons, generation of repetitive DNA by recombination, and transferring of foreign sequences from plastid or nuclear genomes or via horizontal exchange of mitochondrial DNA (see [34] for discussion). However, it is unlikely that plasmids contributed much into the Siberian larch mitogenome size as we found relatively few plasmid-like insertions, representing only 0.11% of the entire mitogenome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most angiosperm mt genomes contain 24 to 41 protein coding genes, three rRNA genes, and two or three rRNA genes [ 2 , 3 , 4 , 5 , 6 , 7 ]. Recent mitochondrial genome studies have demonstrated horizontal gene transfer (HGT) and intracellular gene transfer (IGT) [ 5 , 8 , 9 , 10 , 11 ]. Additionally, plant mitochondria contain mitochondrial-encoded cytoplasmic male sterility (CMS) genes, which are related to the production of functional pollen or functional male reproductive organs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This year saw a number of mitochondrial genomes published in short succession ( Guo et al. 2020 ; Kan et al. 2020 ; Sullivan et al.…”
Section: Introductionmentioning
confidence: 99%